PENGEMBANGAN MATERI AJAR TEKS PROSEDUR BERBANTUAN WEBSITE GOOGLE SITES PADA KELAS VII SMP NEGERI 1 PERCUT SEI TUAN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop instructional materials for procedural texts with the aid of the Google Sites website for grade VII junior high school students. This research is a development study (R&D) using the ADDIE research procedure, which has been simplified into three stages, namely analysis, planning, and development. The subjects of this study were the validators who provided valid results, consisting of content experts, media experts, and Indonesian language teachers at SMP Negeri 1 Percut Sei Tuan. The data collection techniques used were interviews with subject teachers and questionnaires distributed to students to identify their needs. The results of this study indicate that the product developed is categorized as highly feasible, with scores from content validators at 90.5%, media experts at 91%, and subject teachers at 97%. Therefore, the average score obtained is 92.83%, indicating that the product is highly suitable for use in learning.